1996
DOI: 10.1007/bf02660892
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality multidimensional image analysis of cortical and subcortical plasticity in the rat brain

Abstract: In this work, we developed and implemented a multimodality multidimensional imaging system which is capable of generating and displaying anatomical and functional images of selected structures and processes within a vertebrate's central nervous system (CNS). The functional images are generated from [14C]-2-deoxy-D-glucose (2DG) autoradiography whereas the anatomic images are derived from cytochrome oxidase (CO) histochemistry. This multi-modality imaging system has been used to study mechanisms underlying info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Our setup requires the virtual alignment of stacked images. Fiducial markers have been shown to be valuable for image stack registration and to overcome known alignment problems such as the "banana" problem (e.g., Toga and Arnicar 1985;Brändle 1989;Ford-Holevinski et al 1991;Humm et al 1995;Goldszal et al 1996;Streicher et al 1997;Rau et al 2013). Our results confirmed that the use of external markers can increase alignment quality.…”
Section: Alignment Qualitysupporting
confidence: 76%
“…Our setup requires the virtual alignment of stacked images. Fiducial markers have been shown to be valuable for image stack registration and to overcome known alignment problems such as the "banana" problem (e.g., Toga and Arnicar 1985;Brändle 1989;Ford-Holevinski et al 1991;Humm et al 1995;Goldszal et al 1996;Streicher et al 1997;Rau et al 2013). Our results confirmed that the use of external markers can increase alignment quality.…”
Section: Alignment Qualitysupporting
confidence: 76%
“…• the slice-order-preferred (Goldszal et al 1996) and • the combined modality-and-slice-order-preferred (Humm et al 2003, Dubois et al 2007.…”
Section: Multi-modality Registration Strategies For 2d Image Stacksmentioning
confidence: 99%
“…Two-dimensional imaging techniques such as autoradiography are generally amenable only to single-parameter image acquisition due to different tissue-sample preparation procedures. Nevertheless, to provide quasi-simultaneous imaging, adjacent brain slices are often imaged by different modalities (Goldszal et al 1996, Dehnhardt et al 2007. This results in interleaved stacks of multi-modality slices with different slice-to-slice image characteristics or, alternatively, multiple single-modality stacks of slices with different stackto-stack characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…fiducial markers: The use of fiducial markers helps increase the reliability of the registration process (Ford-Holevinski et al, 1991;Goldszal et al, 1996Goldszal et al, , 1995Humm et al, 1995). In histology, physical markers (straight rigid needles for instance) can be inserted into the organ to be processed, prior to the slicing step.…”
Section: Registration Algorithms For 3-d Reconstructionmentioning
confidence: 99%